If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3p + 9 + -2p = 11 + -7 Reorder the terms: 9 + 3p + -2p = 11 + -7 Combine like terms: 3p + -2p = 1p 9 + 1p = 11 + -7 Combine like terms: 11 + -7 = 4 9 + 1p = 4 Solving 9 + 1p = 4 Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + 1p = 4 + -9 Combine like terms: 9 + -9 = 0 0 + 1p = 4 + -9 1p = 4 + -9 Combine like terms: 4 + -9 = -5 1p = -5 Divide each side by '1'. p = -5 Simplifying p = -5
| [7*(8+8)]+9=y | | 36x^2-196x=0 | | k/4+2(3k-1)/3 | | x^5+3x-9=0 | | 4x+7x-58=107 | | 7.62*3.14= | | 23-2a=3(6a-4) | | x/4+4=7-z/4 | | 12x-109-6x=71 | | 44=3(-4n-7)-7(-7n-4) | | x-(x*.15)=150 | | 10/1.167 | | 6(h-2)=6 | | 4x+8=x+9 | | -83-9x-3x=193 | | 4y-36x=28 | | 0=2x^2+4xh-A | | 16b^2=36+36b | | -12x+x-71=127 | | 5(x-3)+4(x-3)=3(x-1) | | 5.6+z=8 | | 30n^4+24n^2= | | y=0.43x+0.57 | | 7(3+x)+(5-4x)= | | 5x+3x/2=20 | | x/2-6=x/7-1 | | y=0.43x+0.43 | | x/6+2/3+3/4x | | 8b/3+7=31 | | x/2-6-x/7-1 | | 2(6v-1)-(v-1)=54 | | 3.8x=2.5x+11.7 |